2017
DOI: 10.5152/dcbybd.2017.1328
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression in Intensive Care Unit Staff

Abstract: Amaç: Sağlık çalışanları arasında stres, anksiyete ve depresyon sık görülen sorunlardır. Yoğun bakım üniteleri (YBÜ) ağır hastalarla uğraşan birimler olarak sağlık kurumları içinde ayrıca stresli çalışma birimleridir. Bu çalışmada, YBÜ çalışanlarında anksiyete ve depresyon sıklığını ve etki eden risk faktörlerini araştırmak amaçlan-mıştır. Gereç ve Yöntemler:Hastanemiz YBÜ çalışanları kesitsel çalışmaya dâhil edildi. Kişilerin demografik özellikleri yanı sıra tıbbi öyküleri ve sigara içme durumları kaydedildi.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…It has been reported that intensive care workers have higher anxiety levels more frequently than other healthcare professionals due to the need to care for serious and terminally ill patients, the need to make quick decisions, and the frequent execution of interventional procedures that increase the risk of transmission (19). Our study's high frequency of intensive care workers with high anxiety levels seems to be compatible with this literature information.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It has been reported that intensive care workers have higher anxiety levels more frequently than other healthcare professionals due to the need to care for serious and terminally ill patients, the need to make quick decisions, and the frequent execution of interventional procedures that increase the risk of transmission (19). Our study's high frequency of intensive care workers with high anxiety levels seems to be compatible with this literature information.…”
Section: Discussionsupporting
confidence: 90%
“…It is a self-report scale consisting of 21 items that evaluate the risk of depression and the severity of depressive symptoms. Depression degrees can be determined as mild (10)(11)(12)(13)(14)(15)(16), moderate (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), and severe according to the scale score (14).…”
Section: Beck Depression Inventory (Bdi)mentioning
confidence: 99%
“…These patients are very closely monitored and cared for while supporting and improving their vital functions with special treatment and care teams. 1 The teams working in intensive care units (ICUs) consist of individuals from various professions collaborating in a multidisciplinary fashion. The primary objective of these teams is to deliver personalized and comprehensive healthcare services to patients.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, nurses are the occupational group that stays together with the patient for the longest time and works in close contact (Lai et al, 2020;Temel & Ertin, 2020). This situation may cause nurses to increase their fear and anxiety levels and experience death anxiety (Ergun et al, 2016;Sharif et al, 2016). Thus, the COVID-19 Pandemic has resulted in widespread depression, fear of COVID-19 and anxiety (Ahorsu et al, 2020).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%